(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
Understanding the linguistic componential traits that influence expressive skills in English as a foreign language is crucial for effective language instruction and acquisition. This study investigates both the commonalities and distinct features that contribute to the development of expressive proficiency in English among foreign language learners. Drawing upon a comprehensive review of existing literature and empirical data, this research identifies key linguistic components such as vocabulary breadth, syntactic complexity, phonological accuracy, and pragmatic competence. Additionally, it explores how these traits interact with socio-cultural factors and individual differences in language learners. By examining the overlap and uniqueness of these linguistic components, this study offers insights into pedagogical approaches that can enhance the teaching and learning of English as a foreign language. The findings underscore the importance of a holistic approach that addresses the multifaceted nature of language proficiency, thereby fostering more effective communication skills in English learners